EVALUATION OF SPATIAL POLICY FOR STREET VENDORS AT THE BULAK FISH CENTER SURABAYA - Hambali Hambali; Subianto Subianto; Chomariah Chomariah (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Arrangements for street vendors are very important, this is because their existence often violates regulations and is not in place. This research is a type of descriptive research using qualitative methods. The research location is at the Bulak Fish Center (SIB) in the city of Surabaya. This research is based on the phenomenon of the Bulak Fish Center which is empty of traders and visitors. The purpose of this research is to find answers on how the policy of providing space for street vendors at SIB Surabaya has succeeded as expected. Data collection techniques were carried out by observation, interviews, and analyzing data contained in the archives and documentation of activities at SIB. The results of the study indicate that the expected benefits of the SIB development in Surabaya are still not effective. Still less efficient and less productive as expected and sometimes traders feel at a loss because the results are not in line with what is expected. So that the policy of providing space for street vendors at SIB Surabaya according to traders is still not right. The inhibiting factors are the lack of participation of the traders to occupy the booth, the lack of socialization, guidance, control, and law enforcement. easy access for traders as well as for prospective buyers/tourists who will go to SIB. Keywords: Collaboration, beach tourism, ecotourism, local wisdom.